Sympathetic ophthalmia following repeated pars plana vitrectomy : Clinical findings and spectral domain OCT follow-up - Bergua, A.; Mardin, C.; Holbach, L.; Meiller, R.; Hohberger, B. (Ophthalmologe, 2016)
Sympathetic ophthalmia is a rare form of bilateral granulomatous panuveitis, occurring after penetrating trauma. Hitherto, sympathetic ophthalmia after vitrectomy has only occasionally been described in the literature. This case report presents a female patient with sympathetic ophthalmia after repeated pars plana vitrectomy on the basis of clinical findings and follow-up with fluorescein angiography, spectral domain OCT, and histopathology.
EVALuna2:21309